KEMAPUAN PRODUKSI SUMBER PANGAN POKOK DAN NON BIJI- BIJAN TERHADAP KETAHANAN PANGAN KABUPATEN BANYUMAS - Adi Poernomo; Hari Winarto (FEB UNWIKU PURWOKERTO, 2020)
This research is based on the problem of food insecurity due to the growing population growth rate which is not balanced by the accelerated growth of food production. This study aims to analyze the effect of rice production, non-rice food crops, agricultural land, and labor absorbed in the agricultural sector against food security in Banyumas regency. Secondary data is sourced from Badan Pusat Statistik. The analyzing tool used is panel data regression with a panel of sub-district in the Banyumas Regency. The analysis results show; There is a positive influence between the variables of rice production, non-rice crop production, and the area of agricultural land (rice field) on the level of food security; While for a variable amount of labor of agricultural sector negative effect to the food security level.